Dose and normal tissue complication probability analysis of various radiotherapy regimens for thymomas - Xiandong, Wu; Haifeng, Luo; Wang, Zhichao; Chao, Li; Yan, Hu; Jingjing, Li (Frontiers in Oncology, 2026)
ObjectiveThis study aimed to compare dosimetric differences and normal tissue complication probability (NTCP) among coplanar intensity-modulated radiation therapy (CO-IMRT), non-coplanar IMRT (NONCO-IMRT), coplanar volumetric-modulated arc therapy (CO-VMAT), and non-coplanar VMAT (NONCO-VMAT) in thymoma radiotherapy and clarify the value of non-coplanar plans.MethodsForty-eight post-thymoma surgery patients were enrolled in this study. Four radiotherapy plans (50 Gy/25 fractions) were made for each patient. The target conformity index (CI), homogeneity index (HI), and organ-at-risk (OAR) (lungs, heart, etc.) dose parameters were then evaluated. NTCP was calculated using the Lyman–Kutcher–Burman (LKB) model. Statistical analysis was performed using the Student–Newman–Keuls (SNK-q) test (p < 0.05 for significance).ResultsThere were no significant clinical differences in target volume coverage and homogeneity among the four plans. The lung V20, heart V30, spinal cord Dmax, and esophagus Dmax of the VMAT techniques were all lower than those of IMRT (p < 0.001). The breast dose of CO-VMAT was significantly higher, while the breast parameters of NONCO-VMAT were close to those of IMRT. NTCP results were consistent with dosimetric findings: VMAT plans had lower NTCP for the heart, spinal cord, and esophagus; moreover, the breast NTCP of CO-VMAT was significantly increased (1.75%), while that of NONCO-VMAT decreased to 0.28%, which was similar to that of IMRT.ConclusionAll four plans meet the thymoma target dose requirement. However, NONCO-VMAT is preferred for its advantages in multi-organ protection and balanced breast dose. Additionally, CO-VMAT should be used cautiously in female patients due to the higher breast dose.